The Influence of Financial Literacy on Consumptive Behavior in Gen Z in Medan City - Zakia Fadila; Prianda Pebri; Ahmad Rivai; Amin Hou; Deby Siska Oktavia Pasaribu (ProBisnis : Jurnal Manajemen, 2023)
Research to determine the effect of financial literacy on Gen Z Consumptive Behavior in Medan City. This type of research is Qualitative. The population was 896 people and the sample used accidental sampling as many as 100 Gen Z who were respondents in this study, the data analysis technique used multiple regression tests and hypothesis testing. The results showed that financial literacy has a positive and significant effect on Consumption Behavior on Gen Z products in Medan City. The results of the determination test above show that the coefficient of determination (seen from R Square) is 0.560, this means that 56% of the variance in the value of Consumption behavior on Gen Z in Medan City is determined or explained by the independent variable, namely Financial Literacy, while the remaining 44% is influenced by other variables not examined in this study such as economy and occupation